Biomechanical properties of growing and decaying roots of Cynodon dactylon - Viroon Kamchoom; David Boldrin; Anthony Leung; Chanakan Sookkrajang; Suched Likitlersuang (My University, 2021)
Abstract AimWe measured the effects of growth and decay on the tensile strength of roots of Cynodon dactylon , considering different mortality causes common to agricultural land conversion (i.e., burning and herbicide application). Drivers of root strength changes have also been studies, including root chemical composition (i.e., cellulose and lignin).MethodWe applied three treatments to C. dactylon grass: (i) growth duration (60, 120 and 180 days), (ii) decay duration after burning (30, 60, 120, 180 and 360 days) and (iii) decay duration after herbicide application (15, 30 and 60 days). After each treatment, diameter, tensile strength, cellulose content and lignin content from root samples were measured (n = 303).ResultsIrrespective to the treatments, strength-diameter relations followed a negative power law (R 2 > 0.6). Increase in the median strength values due to grass growth was consistent with the increases in both the cellulose and lignin contents. Root decay caused by herbicide applications caused significantly greater and faster reduction in strengths than by burning treatment, because of the faster reduction of both the cellulose and lignin contents.ConclusionRoot decay due to different causes of plant mortality can increase the susceptibility to erosion and slope instability during conversion of agricultural land. Measures on slope safety and erosion are vital when applying herbicides for weed clearance in farmlands because of faster deterioration of root chemical composition and root strength (compared to burning).
Keywords: Cynodon dactylon; Tree Root and Stability Studies